A dual-pillar method for measurement of stress-strain response of material at microscale. (November 2019) - Chu, Kangjie; Yan, Kai; Ren, Fuzeng; Sun, Qingping
Abstract: A dual-pillar method is proposed to determine nonlinear stress-strain relation and mechanical properties of shape memory alloy at microscale. Two neighboring cuboidal micropillars of the same cross-sectional area but different heights are fabricated and compressed by flat-tip nanoindentation. An accurate stress-strain response of the middle uniformly deformed part of the long pillar is obtained by subtracting the measured displacement of the short pillar from that of the long pillar to remove the top and bottom effects. Finite element analysis confirmed the effectiveness of the developed dual-pillar method in removing the effects of substrate deformation and stress concentration in single-pillar compression. This method is also valid to other materials and to tensile loading condition. Graphical Abstract: Unlabelled Image